Information as a difference: toward a subjective theory of information. Issue 4 (4th July 2019) - McKinney, Earl H.; Yoos, Charles J.
ABSTRACT: We propose a difference theory of information that extends Gregory Bateson's definition that information is any difference that makes a difference. Information arises from conception of difference, criteria, and meta criteria. Individuals perceive differences and conceive information from those differences. A first difference is a perceived difference that leads to a second difference – a changing mind. The difference theory provides a theoretical foundation for distinguishing the terms data and information. Additionally, it describes how individuals inform in uncertainty by applying and sometimes recursively applying criteria levels. We apply the difference theory to IS practice and research contexts.